Ketoprofen in the Cat: Pharmacodynamics and Chiral Pharmacokinetics - Lees, Peter; Taylor, Polly Monroe; Landoni, Maria Fabiana; Abdul Kadir, Arifah; Waters, C. (Elsevier Science, 2003)
The non-steroidal anti-inflammatory drug ketoprofen (KTP) was administered as the racemate to cats intravenously (IV) and orally at clinically recommended dose rates of 2 and 1 mg/kg, respectively, to establish its chiral pharmacokinetic and pharmacodynamic properties.